POLICE, BUSINESSPERSON, AND THEIR ROLE IN CORRUPT NETWORK IN RUSSIA (Journal of actual problems of jurisprudence, 2023)
This study examines crime and corruption in Russian Civil Service and Law Enforcement following the legal/police reforms. It demonstrates the transformation of Organized Crime in Russia into new corrupt network of organized crime, law enforcement and government officials in stark contrast to the original policy intent.The purpose of this study was to assess the scale and threat of crime and corruption in Russian law enforcement; the work has also classified the OCN nature, structure, scale and method of operation. Findings from this project will be submitted for publication.Key words: crime, corruption, organized crime, police reforms, law enforcement, Criminal Networks, transit crime, economic crimes